Urban floristic in the western area of the municipality of Poços de Caldas, MG - Bucci, Maria Elisa Diniz; Botezelli, Luciana; Clemente, Felipe; Braga, João Paulo de Lima; Williams, Eric Arruda (Ciência e Natura, 2020)
The urban afforestation is an important tool for the formation of a city with an environmental quality. The present project has the aim to provide the qualitative inventory of all tree species and their respective families, in the neighborhood of Véu das Noivas, located in the west region of the municipality of Poços de Caldas, Minas Gerais. For each tree, geographic coordinates were collected and the species identified, with the help of experts, and with the material available in “Jardim Botânico de Poços de Caldas” foundation and bibliographies. Together, all species make a total of 497 individuals, once 185 in green spaces, 211 were located close to public highways and 101 were located close to the walls of some buildings. Among these trees, 44 species were found in green spaces, 54 in streets and 19 in vertical landscaping, distributed in 27 families present in green areas, 25 in streets and 14 in vertical landscaping. It was also noticed exotical species compose most part of the analyzed trees. It’s important to remember that the usage of adequate species in urban afforestation is directly related to a correct urban planning.